2018
DOI: 10.1155/2018/7490961
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Mucosal Resection Performed Underwater for Nonampullary Duodenal Epithelial Tumor: Evaluation of Feasibility and Safety

Abstract: Objectives Recently, opportunities to encounter superficial nonampullary duodenal epithelial tumor (SNADET) have increased. EMR and ESD are performed to treat SNADET. However, the rate of perforation is higher than that of other gastrointestinal lesions, regardless of which method is used. Underwater EMR (UW-EMR) is immersion treatment of SNADET, which has low risk of perforation and can remove lesions safely and completely. In the present study, we retrospectively investigated patients in whom UW-EMR was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 11 publications
2
31
0
Order By: Relevance
“…In previous reports, UEMR was reported to be safe, even without the use of submucosal injection. [16][17][18] However, these studies included fewer than 31 cases, even in the largest case series. It was impossible to accurately estimate the incidence rate of perforation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous reports, UEMR was reported to be safe, even without the use of submucosal injection. [16][17][18] However, these studies included fewer than 31 cases, even in the largest case series. It was impossible to accurately estimate the incidence rate of perforation.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a concern that the risk of perforations might increase. Although some studies have indicated that UEMR can be done safely, even for duodenal lesions, [16][17][18] these studies included a relatively small number of cases; therefore, they did not permit a discussion of complications with low incidence rates. Consequently, detailed treatment outcomes of UEMR and appropriate treatment strategies for small SNADET are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The strategy of endoscopic treatment for duodenal tumor has been controversial because of insufficient evidence. It has been reported that simple UEMR using floating force underwater condition is useful and safe even for duodenal tumor with non-lifting sign [7, 8]. However, we reported that en bloc resection rate of UEMR is significantly lower than EMR for duodenal tumor [9].…”
Section: Discussionmentioning
confidence: 91%
“…Recently, cold snare polypectomy (CSP), which does not involve local injection nor the use of an electrosurgical generator, 5,6 and underwater EMR (UEMR), in which snaring is performed under water without local injection to the submucosal layer, 7,8 have been performed. Criteria for each procedure are being established.…”
Section: Current Status Of Therapeutic Endoscopy For Duodenal Lesionsmentioning
confidence: 99%